PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP MINAT BERWIRAUSAHA PESERTA DIDIK KELAS XII PEMASARAN DI SMK NEGERI 3 PONTIANAK - Yulandari, Febrianti; Buwono, Sri; Witarsa, Witarsa (Universitas Tanjungpura, 2023)
This study aims to determine the effect of the use of social media on the entrepreneurial interest of class XII at SMK Negeri 3 Pontianak. This study uses a quantitative approach with the type of correlational method. The subjects of this study were students of class XII marketing at SMK Negeri 3 Pontianak with 67 respondents. Questionnaire sent using the google form application. The results of this study indicate: 1) the use of social media is 74,39% in the high category, 2) the interest in entrepreneurship is 75,90% in the high category, and 3) the use of social media has a significant influence on the entrepreneurship interest of class XII students at SMK Negeri3 Pontianak is 0,427 or if the percentage is 42,7% and the rest is influenced by other factors that are not discussed further in this study. A significant value of 0,000 0,05 which means it is accepted. It is concluded that the use of social media affects the entrepreneurship interest of class XII students marketing at SMK Negeri 3 Pontianak.